Manufacturing methods for machining micro pits of hip implant for metal-on-metal lubrication - Nor Liyana, Safura Hashim; Azli, Yahya; Mohammed Rafiq, Abdul Kadir; Syahrullail, Samion; Nazriah, Mahmud (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/